Degradation Study of Biodegradable Plastic Using Nata De Coco as A Filler - Tiara Nur Elfiana; Anisa Nur Izza Fitria; Endaruji Sedyadi; Susy Yunita Prabawati; Irwan Nugraha (Biology, Medicine, & Natural Product Chemistry, 2018)
Starch is known as a biodegradable raw material that can be degraded by bacteria and microorganisms in the soil. Starch has cellulose which is kind of plant cellulose. This study shows the biodegradation rates of plastic made from Ganyong Canna (Canna edulis Kerr) as a cellulose source which is added with nata de coco as a filler. The biodegradable plastic functional group was confirmed by using FITR. The results show that the O-H group of Ganyong Canna (Canna edulis Kerr) biodegradable plastic is located at wave number 3298.03 cm-1 and shifted to 3290.32 cm-1 after addition of nata de coco. The C-H bonds functional groups in Canna biodegradable plastics and nata de coco plastics are at wave numbers 2920.01 cm-1 and 2916.16 cm-1. While the C-O bonds functional groups in biodegradable starch plastics and nata de coco is shown at wave numbers 995.05 cm-1. The mechanical properties of biodegradable plastics testing are thickness, tensile strength, and elongation based on the ASTM method. The thickness is about 0.1005 mm, the tensile strength of biodegradable plastic is 4,3244 MPa and the elongation value range about 13.9639% while the WVTR range about 14.20 g/m² hours. The results show that the increase of the plastic degradation made from nata de coco occurs between 5% - 38% per days. It is faster than the plastic made from pure Ganyong Canna (Canna edulis Kerr) starch. These results indicate that nata de coco could be added in biodegradable plastic on packaging materials for better degradation.